Heidegger's Hermeneutic Phenomenology and the Application to Ghanaian Women's Experiences of Unsuccessful Invitro Fertilisation (IVF) Treatment - Amoah, Vida Maame Kissiwaa (Department of Health and Rehabilitation Sciences, 2020)
Ghanaian women experiencing infertility problem, have been seeking invitro fertilisation treatment in the quest for motherhood, however there is a dearth in the nursing studies researching this phenomenon. It appears that the concept and meanings of infertility is inadequately explored from the perspective of women experiences following unsuccessful invitro fertilisation treatment. In particular, it is vital to be knowledgeable about the challenges women encounter when undergoing IVF treatment and following unsuccessful procedure. The study sought to gain a deeper knowledge and to understand the meanings women struggling with infertility and its treatment experience and how invitro fertilisation treatment failure affects women in their everyday life. To unearth the women perception and meaning attributed to their experiences of unsuccessful infertility treatment, Heidegger's philosophy of phenomenology underpinned this study. A semistructured opening question and further probing questions were used to gather information which was reduced to sub-themes and main themes which captured the participant's lived experiences of unsuccessful invitro fertilisation treatment. I adopted van Manen's (1990) six steps of research activities as a structure to unravel the participants' phenomenological conversations. Applying Heidegger's concept of the three modes of existence (Existenze): authenticity, inauthenticity and undifferentiatedness, four major themes were identified: 1. Seeking wholistic and authentic care- authenticity 2. Facing up to the Angst- inauthenticity 3. The vulnerable self - inauthenticity 4. Living with infertility (being-in-the-world-of-motherless) - undifferentiatedness The participants' phenomenological conversations and their stories have revealed a range of challenges Ghanaian women who seek invitro fertilisation treatment go through. The study contribute significantly by giving insight to the painful experiences Ghanaian women go through when seeking invitro fertilisation treatment and has given a voice to how assisted reproductive technologies are currently experienced in the Ghanaian context. From the women's narrative, it appeared that their emotional and informational needs were not being met and were not being cared for as expected. The findings provide some direction regarding the needs of women experiencing infertility for information, support and advocacy in their pursuit of assisted reproductive technology services in Ghana. There is a critical need to simplify invitro fertilisation treatment and provision of safe, affordable procedure so that the average Ghanaian women can access it.